2018
DOI: 10.1590/1807-3107bor-2018.vol32.0044
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine and proanthocyanidin enhance the long-term bond strength of resin-based endodontic sealer

Abstract: The aim of this study was to evaluate the effects of proanthocyanidin (PA) and chlorhexidine (CHX) on the bond strength (BS), failure pattern, and resin-dentin interface morphology of the endodontic sealers EndoREZ and AH Plus after 24 h and 6 months of water storage. A total of 120 prepared bovine roots were divided into six groups: AH Plus, CHX+AH Plus, PA+AH Plus, EndoREZ, CHX+EndoREZ, and PA+EndoREZ. Dentin was treated for 1 or 5 min with 2% CHX or 15% PA, respectively. Roots were filled and stored in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Previous studies demonstrated that CHX improves the bond strength of resin-based cements and composite resins to dentin. 18 , 19 In the present study, 2% CHX and 0.4% chitosan showed similar results in all the sections. There was no significant difference in the bond strength of CHX combinations with chitosan between two different concentrations.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies demonstrated that CHX improves the bond strength of resin-based cements and composite resins to dentin. 18 , 19 In the present study, 2% CHX and 0.4% chitosan showed similar results in all the sections. There was no significant difference in the bond strength of CHX combinations with chitosan between two different concentrations.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is in agreement with the result of previous studies comparing the bond strength of these two subgroups of resin-based sealers. [ 29 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the application of solution for 5 minutes was used based on previous studies 42 43 that applied other agents in a similar time, determining a potential effect of different compounds. However, future investigations could evaluate the behavior of agents with other application times, examine their use associated with other adhesive systems, or compare them with other agents already used for this purpose, such as chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%